Exergoenvironmental, environmental impact and damage cost analyses of a micro turbojet engine (m-TJE). (November 2022) - Balli, Ozgur; Kale, Utku; Rohács, Dániel; Karakoc, T. Hikmet
Abstract: This study presents a comprehensive investigation of the emission impact, environmental damage cost, exergoenvironmental and life cycle assessment (LCA) analyses of a micro turbojet engine (m-TJE) utilized on Unmanned Air Vehicle (UAV) for four different operating cases. The novelty and motivation to conduct this study are that no study in the literature was done about the environmental damage cost and exergoenvironmental analyses based on exergy and LCA of a micro turbojet engine used on UAVs. According to the results of this study, the engine product exergy rate increasing from 27.119 MJ/h at Case-1 to 114.742 at Case-4 while the engine's specific emission impact (sei) value decreases from 13.346 mPts/MJ at Case-1 to 5.440 mPts/MJ at Case-4. Similarly, the specific environmental damage cost of engine product decreases from 0.150 /MJ at Case-1 to 0.061 /MJ at Case-4 whilst the specific exergy cost of engine product goes down from 0.249 /MJ at Case-1 to 0.088 /MJ at Case-4. In this regard, the specific exergoenvironmental cost of engine product declines from 0.400 /MJ at Case-1 to 0.150 /MJ at Case-4. Besides, the specific exergoenvironmental impact of engine product reduces from 71.694 mPts/MJ at Case-1 to 29.219 mPts/MJ at Case-4 when the relative exergoenvironmental impact difference of engine product falters from 1257.306 % at Case-1 to 453.162 % at Case-4. This investigation shows that an increase in engine product rate reduces specific emission impact, specific environmental damage cost, specific exergy cost, specific exergoenvironmental impact, and relative exergoenvironmental impact difference of engine production. Highlights: A micro turbojet engine is investigated for different operating cases. Specific emission impact value decreases from 13.346 mPts/MJ at Case-1 to 5.440 mPts/MJ at Case-4. Specific environmental damage costs were reduced from 0.150 /MJ at Case-1 to 0.061 /MJ at Case-4. Specific exergoenvironmental cost declines from 0.400 /MJ at Case-1 to 0.150 /MJ at Case-4. Specific exergoenvironmental impact goes down from 71.694 mPts/MJ at Case-1 to 29.219 mPts/MJ at Case-4.